Biological indicator records (diatoms, chrysophyte cysts, freshwater invertebrates) from sediments of Suzdalevo Lake (Tunguska region, Russia) – sediment core SUZ1 - Radana Kavková; Daniel Vondrák; Barbora Chattová; Eva Svecova; Marian Takac; Viktor Golias; Richard Štorc; Carlo Stanghellini; Gunther Kletetschka (PANGAEA, 2022)
Here, we present diatom (Bacillariophyceae), chrysophyte (Chrysophyceae), and zoological indicator (Chironomidae, other aquatic insect, planktonic crustaceans, Bryozoa, Rhabdocoela) taxonomic datasets from a sediment core (core ID: SUZ1, length of 0.42 m) record from a shallow lake (Suzdalevo Lake, 1.8 ha, max. depth of 2.3 m) located near the epicenter of the Tunguska Event explosion in 1908 CE (60°39'29.05''N, 102°3'3.36''E). The datasets include primary data presented in an article (Kavková et al. 2022) that is focused on formation process of the study site (potential impact lake) and Tunguska Event-related environmental disturbance. The core was retrieved using a Kajak gravity corer (sampling tube diameter of 5.8 cm and length of 50 cm) in May 2019.